1990
DOI: 10.1182/blood.v75.8.1711.bloodjournal7581711
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of sickle cell membranes

Abstract: The mechanical properties of sickle erythrocyte membranes were evaluated in the ektacytometer. When ghosts from the total red blood cell population were examined, the rigidity of the resealed ghosts and their rate of fragmentation by shear stress (t1/2) were normal. However, fractionation on Stractan density gradients revealed that sickle cells were heterogenous in their membrane mechanical properties. The ghosts from dense cell fractions exhibited both increased rigidity and decreased stability. Presumably, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Sickle RBCs are mechanically fragile, and dense sickle RBCs are particularly susceptible to mechanical damage, probably because of decreased membrane stability. 30 Because patients with SS and α-thalassemia have decreased numbers of dense cells, it is likely that their RBCs are less mechanically fragile. This, in turn, may be a contributing factor to the decreased hemolytic rate observed in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Sickle RBCs are mechanically fragile, and dense sickle RBCs are particularly susceptible to mechanical damage, probably because of decreased membrane stability. 30 Because patients with SS and α-thalassemia have decreased numbers of dense cells, it is likely that their RBCs are less mechanically fragile. This, in turn, may be a contributing factor to the decreased hemolytic rate observed in these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…They found that cellular dehydration and the consequent increase in cytoplasmic viscosity are major determinants of the abnormal rheologic behavior of oxygenated sickle cell anemia RBC. Studies on resealed ghosts showed that membrane changes of sickle cell anemia RBC, such as altered material properties, increased extensional rigidity, and decreased membrane stability (53,89), contribute to the abnormal deformability of sickle cell anemia RBC.…”
Section: Factors That Affect Rbc Deformabilitymentioning
confidence: 99%
“…Besides being poorly deformable, oxygenated sickle cell anemia RBC are susceptible to mechanically induced cell fragmentation. In vitro studies have documented increased sensitivity of sickle RBC to mechanical fragmentation following exposure to fluid shear stress (89). The most dense cells are most susceptible to mechanical damage, probably due to weakening of the skeletal protein interactions (spectrin-spectrin or spectin-actin-protein 4.1) as a result of accumulated oxidative damage.…”
Section: Mechanical Fragility Of Sickle Rbcmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to cell suspension studies, viscometry is also useful for determining the rheological properties of Hb S solutions (Briehl, 1981;Chien et al, 1982;Danish et al, 1987;Drasler et al, 1989). Recent experimental studies have shown that the overall rheological properties of sickle erythrocytes are strongly influenced by both cell membrane viscoelasticity (Nash et al, 1984;Evans et al, 1984;Drasler et al, 1989;Messmann et al, 1990;Hebbel, 1991) and interior Hb S gelation (Briehl, 1981;Hofrichter et al, 1981;Gabriel et al, 1981;Noguchi and Schechter, 1985;Hofrichter, 1987, 1990;Danish et al, 1987Danish et al, , 1989Clark, 1989).…”
Section: Experimental and Theoretical Backgroundmentioning
confidence: 99%